Improving Student Abilities in Plant Anatomy Courses Using a Collaboration of Research-Based Learning Models and Gamification Techniques - Nau, Getrudis Wilhelmina; Sepe, Florentina Yasinta; Missa, Hildegardis; Santos, Americo dos (Al Jahiz, 2024)
The quality of education in NTT is still low and needs to be improved. One of them is by improving the quality of learning through the collaboration of innovative learning models. The focus of this study was to determine the increase in students' abilities in plant anatomy courses using collaborative research-based learning models and gamification-based assessment techniques. This pre-experiment research used a qualitative research approach. The research sample was determined using purposive sampling technique with one group pretest-postest design. The test data were analyzed descriptively. The results showed that there was a difference in the average pretest of 40.5 and posttest of 80.5. The results of the n-gain calculation obtained a score of 0.6 with the gain category being moderate. Classically, the class was complete with a percentage of 100%. The conclusion of the results of this study is that there is an effect of blended learning strategies through the collaboration of research-based learning models and gamification-based assessment techniques on student learning outcomes in the Unwira Biology Education Study Program.